CD81 T Cells Provide an Immunologic Signature of Tuberculosis in Young Children - Lancioni, Christina; Nyendak, Mellisa; Sarah Zalwango, Sarah Kiguli; Mori, Tomi; Mayanja-Kizza, Harriet; Balyejusa, Stephen; Null, Megan; Baseke, Joy; Mulindwa, Deo; Byrd, Laura; Swarbrick, Gwendolyn; Scott, Christine; et al. (American Thoracic Society, 2011)
Mycobacterium tuberculosis (Mtb), the etiology of tuberculosis (TB), causes over 9 million cases of disease and 1.7 million deaths annually (1). The only available vaccine to prevent TB, bacillus Calmette-Gue´ rin, offers little protection against the most common disease manifestations (2) and efforts to develop an improved vaccine are hampered by poor understanding of immunologic events that occur after Mtb exposure. Scientific studies of immunologic responses to initial Mtb infection are difficult because most individuals living in TB-endemic settings have experienced multiple Mtb exposures. Young children, however, suffer disproportionately after exposure to Mtb, because they are at substantial risk for developing TB after primary infection (3–5). Therefore, young children with TB offer a valuable window into the human immune response to primary Mtb infection.
Keywords: Mycobacterium tuberculosis; Infant; Child; CD8-positive T lymphocytes; Enzyme-linked immunosorbent spot